Adherence with psychotherapy and treatment outcomes for psychogenic nonepileptic seizures. (12th February 2019) - Tolchin, Benjamin; Dworetzky, Barbara A.; Martino, Steve; Blumenfeld, Hal; Hirsch, Lawrence J.; Baslet, Gaston
Abstract : Objective: We conducted a prospective cohort study of patients with psychogenic nonepileptic seizures (PNES) to examine the association between adherence with psychotherapy and outcomes, including significant (≥50%) reduction in PNES frequency, PNES freedom, improvement in quality of life, and reduction in emergency department (ED) utilization. Methods: A total of 105 participants were referred to receive psychotherapy either at Brigham and Women's Hospital or with a local therapist. We called participants at 12–24 months follow-up and obtained detailed follow-up data from 93 participants (89%). Participants were considered adherent with psychotherapy if they attended at least 8 sessions within a 16-week period starting at the time of referral. Results: Adherence with psychotherapy was associated with reduction in seizure frequency (84% in adherent group vs 61% in nonadherent, p = 0.021), improvement in quality of life ( p = 0.044), and reduction in ED utilization ( p = 0.040), with medium effect sizes; there was no difference in PNES freedom. The association between adherence and ≥50% reduction in PNES frequency persisted when controlling for potential confounders in a multivariate model. Psychotherapy nonadherence was associated with baseline characteristics of self-identified minority status (odds ratio 7.47, p = 0.019) and history of childhood abuse (odds ratio 3.30, p = 0.023). Conclusions: Our study is limited in that it cannot establish a causal relationship between adherence with psychotherapy and outcomes, and the results may not generalize beyond the single quaternary care center study site. Among participants with documented PNES, adherence with psychotherapy was associated with reduction in PNES frequency, improvement in quality of life, and decrease in ED visits.